Structure of an Influenza A virus N9 neuraminidase with a tetrabrachion‐domain stalk. Issue 2 (4th February 2019) - Streltsov, Victor A.; Schmidt, Peter M.; McKimm-Breschkin, Jennifer L.
Abstract : This communication is the first to describe the crystal structure, at 2.6 Å resolution, of a recombinant N9 influenza neuraminidase with an artificial stalk formed by the tetrabrachion (TB) tetramerization domain from Staphylothermus marinus . The structure of the N9 head without the TB domain was also determined at 2.3 Å resolution and both were compared with the N9 head derived from egg‐grown virus, which was resolved to 1.4 Å resolution: the highest resolution ever reported for an uncomplexed N9 head. Abstract : The influenza neuraminidase (NA) is a homotetramer with head, stalk, transmembrane and cytoplasmic regions. The structure of the NA head with a stalk has never been determined. The NA head from an N9 subtype influenza A virus, A/tern/Australia/G70C/1975 (H1N9), was expressed with an artificial stalk derived from the tetrabrachion (TB) tetramerization domain from Staphylothermus marinus . The NA was successfully crystallized both with and without the TB stalk, and the structures were determined to 2.6 and 2.3 Å resolution, respectively. Comparisons of the two NAs with the native N9 NA structure from egg‐grown virus showed that the artificial TB stalk maintained the native NA head structure, supporting previous biological observations.